Pengaruh Buku Bergambar Tanpa Kata Digital untuk Meningkatkan Kemampuan Siswa dalam Menulis Teks Naratif di SMP Islam As-Shofa Pekanbaru - Indri Romansyah Pohan (Madah: Jurnal Bahasa dan Sastra, 2023)
This research aims to introduce teaching media based on technology using digital wordless picture books to improve students’ narrative writing abilities. This teaching media is presented in the form of PDF and e-books. The research design in this research used quasi-experimental. The instrument in this research used writing test. The subject in this research are the eighth-grade students of SMP Islam As-Shofa Pekanbaru. Purposive sampling technique was employed to select the sample. The result of normality test indicate the data is normal distribution and the homogeneity test is homogeneous. The calculation of the Independent Sample T-test shows that the p-value for the posttest data of the experimental group and the control group is p = 0,002 < 0,05. The result of the Independent Sample T-test indicate a that the Digital Wordless Picture Books media is effectively used in improving students’ ability in writing narrative text to the eighth-grade students of SMP Islam As-Shofa Pekanbaru.